Contribution of vitamin B 6 deficiency to anemia in children on regular hemodialysis - Fatma Atia; Hafez Bazaraa; Yara Abdelatty; Sarah Lotfy; Eman Eryan (BMC Pediatrics)
Abstract Background Anemia is prevalent among pediatric patients diagnosed with end-stage kidney disease (ESKD). In addition, erythropoiesis-stimulating agents (ESA) and iron supplementation are considered the cornerstones in the management of anemia. However, a significant proportion of patients remain anemic. Vitamin B6 plays a vital role in the biosynthesis of heme and may be deficient in children with chronic kidney disease (CKD), particularly those on regular hemodialysis (HD). We aimed to evaluate serum vitamin B6 concentration in those children and determine its correlation with anemia indices. Methods The current cross-sectional study included 39 children on regular HD and 43 healthy controls. Clinical data were collected, including anthropometric measurements, blood pressure, iron, and erythropoietin therapy. Laboratory investigations included hemoglobin (Hb) indices, iron profile, and vitamin B6 level. Results The median Hb level in our cohort was 10.5 g/dL, and nine patients had Hb levels at or above the target Hb of 11 g/dl. They had a median Serum Vitamin B6 concentration of 28.2 ng/ml (IQR = 22.8–52.9) compared to a median of 27.5 ng/ml(IQR = 20–34) in controls, with no substantial differences between both groups. There was no statistically significant correlation between vitamin B6 and Hb levels or erythropoietin dose. Conclusion It is evident that the majority of our patients did not meet the desired threshold for anemia control. However, it is noteworthy that the average hemoglobin (Hb) level approached the intended target. The incidence of Vitamin B6 deficiency was not found to be statistically significant within our study population. Therefore, we could not establish a correlation between vitamin B6 deficiency and anemia in children on HD.